Ideologi Pada Novel Ayat-Ayat Cinta: Analisis Wacana Kritis Model Van Dijk - Rina Rosdiana (Indonesian Journal of Applied Linguistics Review, 2022)
The ideology contained in the novel is a central concept in critical discourse analysis. One of the novelists who has a view of the surrounding existence through an ideology is Habiburarahman El Shirazy. The purpose of this research is to find out the form of ideology that underlies the novel Ayat-Ayat Cinta by Habiburahman El Shirazy and to describe the context that triggers the ideology contained in the novel. This research uses Van Dijk's Critical Discourse Analysis theory. This type of research is included in qualitative descriptive research with content analysis techniques. The data in this study are sentences and paragraphs. Based on the research results, it is known that the ideology underlying the novel Ayat-ayat Cinta by Habiburarahman El Shirazy is Islamic ideology. The context that triggers this ideology is how Habiburrahman El Shirazy views perceptions of Muslim and western society towards Islam, views on how to date in Islam, and is based on Habiburrahman El Shirazy's biography. Overall, the novel Ayat-Ayat Cinta is a novel that reminds readers that at least they can change their mindset by reading and understanding the Koran well and implementing Islamic concepts in everyday life.